Scholastic book of world records, 2016 : special edition : epic wins and fails - Morse, Jenifer Corr (Scholastic Inc., 2015)
Contains full-page descriptions of approximately three hundred world records in such categories as pop culture, sports, and science, and includes photographs and illustrations.